2013
DOI: 10.1177/0969733013505310
|View full text |Cite
|
Sign up to set email alerts
|

Operational effectiveness of blended e-learning program for nursing research ethics

Abstract: This study suggested integrating research ethics education in the nursing curriculum as a required course of study for nursing students and as part of the in-service training program for nurses in order to improve research ethics in nursing research in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 17 publications
1
16
0
3
Order By: Relevance
“…Driscoll and Carliner (2005, p.89) stated that Horn and Staker (2011, p.3) who defined blended learning as "any time a student learns at least part at a supervised brick-and-mortar location away from home and at least part through online delivery with some element of student control over time, pace, path, and/or pace". Blended learning has received support from many academics and higher education institutions (Cho and Shin, 2014;Waha and Davis, 2014;ILot et al, 2013). However, systematic reviews have indicated a lack of available evidence to support the blended learning approach to teaching clinical skills in healthcare education.…”
Section: What This Paper Adds?mentioning
confidence: 99%
“…Driscoll and Carliner (2005, p.89) stated that Horn and Staker (2011, p.3) who defined blended learning as "any time a student learns at least part at a supervised brick-and-mortar location away from home and at least part through online delivery with some element of student control over time, pace, path, and/or pace". Blended learning has received support from many academics and higher education institutions (Cho and Shin, 2014;Waha and Davis, 2014;ILot et al, 2013). However, systematic reviews have indicated a lack of available evidence to support the blended learning approach to teaching clinical skills in healthcare education.…”
Section: What This Paper Adds?mentioning
confidence: 99%
“…3,16 It is also aimed at increasing educational effectiveness by supplying additional professor-student interactions, which are not available in e-learning, through face-to-face classes. 18,19 Some previous studies on blended learning in nursing reported an improvement in the safe and accurate administration of medication in newly employed nurses, 11 an increase in ethics education in nursing, 20,21 and an improvement in learning outcomes for skills in terms of the fundamentals of nursing in Korea. 16,22 However, there are few studies on the application of blended e-learning to improve the core basic nursing skills that are required for nursing students who are about to graduate and work as newly employed nurses.…”
mentioning
confidence: 99%
“…Dentre os estudos que utilizaram testes estatísticos como procedimento de análise de dados, 24 aplicaram questionários de pré e de pós-teste com o objetivo de avaliar diferentes aspectos dos cursos, com destaque para a avaliação do ganho de conhecimento (BRESSEM et al, 2016;MCLEOD;MORCK;CURRAN, 2014;LAVENDER et al, 2013;MOREIRA et al, 2015;MICHELAZZO et al, 2015;KULIER et al, 2012;ILOTT et al, 2014;BROWNLOW et al, 2015;WANG et al, 2016;BLAZER et al, 2012;KENEFICK et al, 2014;CHO;SHIN, 2014). Instrumentos de pré e de pós-teste também incluíram perguntas relacionadas às características sociodemográficas dos participantes (BRESSEM et al, 2016;MCLEOD;MORCK;CURRAN, 2014;MOREIRA et al, 2015; O'BRIEN; BROOM; ULLAH, 2015; MATSUBARA; DOMENICO, 2016).…”
Section: Atitudesunclassified
“…Efetividade da formação profissional ofertada na Educação a distância: validação teórica de um instrumento curso (BRESSEM et al, 2016), atitudes e crenças relacionadas à área do curso (BROWNLOW et al, 2015;CHO;SHIN, 2014), habilidades profissionais na área do curso (BROWNLOW et al, 2015;BLAZER et al, 2012;KENEFICK et al, 2014), desenvolvimento de competências profissionais (O'BRIEN; BROOM; ULLAH, 2015) e confiança para trabalhar na área do curso (BROWNLOW et al, 2015;O'BRIEN;BROOM;ULLAH, 2015).…”
Section: Atitudesunclassified